Strategi Pengelolaan Komunikasi dalam Membentuk Personal Branding di Media Sosial Tiktok - Shani Dwi Putri; Suzy Azeharie (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
One of the features that characterize TikTok social media is its main page called For You Page or FYP. Users who are frequently featured on FYP can become popular and have many followers, known as TikTok celebrities. The strategies used by each TikTok celebrity in forming personal branding tend to be different from one another. This research aims to find out the authentic personal branding that TikTok celebrities want to form in their TikTok accounts and the communication management strategies they are doing to form their personal branding on TikTok. This research is conducted because there has not been any research that discussed communication management strategies to form personal branding on TikTok social media before. The theories used in this research are new media theory, personal branding, and communication management strategy Circular Model of SoMe for Social Communication. The research uses descriptive qualitative research approach with case study research method. The datas are obtained from in-depth interviews with five key informants, non-participant observation, documentation, and literature study. The results show that the communication management strategies carried out by each TikTok celebrity was through their interaction and content. The types of interactions differ according to their personal choices and do not always depend on the category of content they create.Salah satu ciri khas media sosial TikTok adalah halaman utamanya yang bernama For You Page atau FYP. Pengguna yang sering ditayangkan dalam FYP dapat menjadi populer dan memiliki banyak pengikut, disebut sebagai seleb TikTok. Strategi yang digunakan setiap seleb TikTok dalam membentuk personal branding cenderung akan berbeda satu sama lain. Tujuan penelitian adalah untuk mengetahui personal branding autentik yang ingin dibentuk seleb TikTok dalam akun TikTok mereka dan untuk mengetahui strategi pengelolaan komunikasi yang dilakukan para seleb TikTok dalam membentuk personal branding masing-masing di media sosial TikTok. Penelitian ini dilakukan karena belum ada penelitian yang membahas mengenai strategi pengelolaan komunikasi dalam pembentukan personal branding di media sosial TikTok.Teori yang digunakan dalam penelitian ini adalah teori media baru, personal branding, dan strategi pengelolaan komunikasi Circular Model of SoMe for Social Communication. Penelitian menggunakan pendekatan penelitian kualitatif deskriptif dengan metode penelitian studi kasus. Data hasil penelitian diperoleh dari hasil wawancara mendalam, observasi non-partisipan, dokumentasi, dan studi kepustakaan terhadap lima narasumber. Hasil penelitian menunjukkan bahwa strategi pengelolaan komunikasi yang dilakukan setiap seleb TikTok adalah melalui interaksi dan konten. Jenis interaksi yang dilakukan berbeda sesuai kehendak pribadi setiap seleb TikTok, serta tidak selalu bergantung pada kategori konten yang dibuat.